Retarding Short-Term Capital Inflows Through withholding Tax - Zee, Howell (IMF Working Papers; Working Paper, 2000)
This paper proposes a price-based measure to mitigate the destabilizing impact of the volatility of global capital movements on the domestic economy of a country pursuing sound economic policies. The measure is a withholding tax on all private capital inflows, with a credit and refund provision that operates within the administrative framework of the existing domestic tax system to relieve noncapital inflows from the tax. This withholding tax, which is substantially more difficult to evade than the much-discussed alternative of imposing non-remunerated reserve requirements, can be implemented with little additional costs to the taxpayers and the tax authorities.